Conceptualization of Economic Growth in Southeast Asia - Bobowski, Sebastian (Konceptualizacja wzrostu gospodarczego w regionie Azji Południowo-Wschodniej, 2010)
The "flying geese" paradigm by Kojima indicates the sequence of processes of economic development in East Asian region. Transfer of technological knowledge and know-how from Japan to neighbouring states, especially "Asian tigers", reflects strengthening intraregional interdependence by rising importance of adaptive capabilities and international trade in context of convergence of regional emerging economies. Optimal direction of institutional factors' influence is to create positive correlation between international trade, intraregional growth dynamics and processes of economic growth, following the experiences of leading regional economies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 9-19
Keywords: "flying geese" paradigm; economic growth; transfer of technology